2023
DOI: 10.3390/toxics11120952
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis of Testes from Mice Exposed to Neodymium Oxide

Shurui Wang,
Ning Bu,
Yudan Yun
et al.

Abstract: (1) Objective: Rare earth neodymium oxide (Nd2O3) is refined and used extensively around the world, and the occupational and environmental safety of rare piles of the earth has attracted considerable attention. Nd2O3 enters the human body through the respiratory system, reaches various organs through blood circulation, and accumulates to produce toxic effects. At present, little is known about the reproductive toxicity of Nd2O3. Non-coding RNAs participate in a variety of physiological activities and are very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Secondly, with the intensive study of epigenetics in disease development, research into non-coding RNA (ncRNA) as a molecular target has become a hot topic. High-throughput sequencing results showed that REE-induced damage was related to abnormal changes in ncRNA expression profiles [102]. For example, in a human bronchial epithelial cell model exposed to nanoparticles of neodymium oxide (NPs-Nd 2 O 3 ), 1915 circRNAs (1025 up-regulated and 890 down-regulated) were abnormally expressed, inducing tissue dysfunction through sponge miRNAs [103].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Secondly, with the intensive study of epigenetics in disease development, research into non-coding RNA (ncRNA) as a molecular target has become a hot topic. High-throughput sequencing results showed that REE-induced damage was related to abnormal changes in ncRNA expression profiles [102]. For example, in a human bronchial epithelial cell model exposed to nanoparticles of neodymium oxide (NPs-Nd 2 O 3 ), 1915 circRNAs (1025 up-regulated and 890 down-regulated) were abnormally expressed, inducing tissue dysfunction through sponge miRNAs [103].…”
Section: Epigeneticsmentioning
confidence: 99%